The Influence of Audit Quality and Audit Committee on the Quality of Financial Reporting of Companies Registered on the Jakarta Islamic Index (JII) - Liahmad,; An-nisa Zhafarina Qashri, (Technium Social Sciences Journal, 2023)
This study aims to determine the impact of the quality of the audit and the audit committee on the quality of financial reporting at companies included in the Jakarta Islamic Index (JII). using the target sampling method. The resulting samples were 26 real estate and real estate companies included in the Jakarta Islamic Index (JII). Hypothesis testing using multiple linear regression. Based on the results of the hypothesis test, it has been found that the quality of the audit, the size of the audit committee, the independent audit committee have no influence on the quality of the financial statements, while the meetings of the audit committee and the experience of the audit committee have a significant impact. had a positive impact on the quality of the financial statements. Participation